Reduction in acute kidney injury post cardiac surgery using balanced forced diuresis: a randomized, controlled trial. (25th November 2020) - Luckraz, Heyman; Giri, Ramesh; Wrigley, Benjamin; Nagarajan, Kumaresan; Senanayake, Eshan; Sharman, Emma; Beare, Lawrence; Nevill, Alan
Abstract: OBJECTIVES: Our goal was to investigate the efficacy of balanced forced diuresis in reducing the rate of acute kidney injury (AKI) in cardiac surgical patients requiring cardiopulmonary bypass (CPB), using the RenalGuard ® (RG) system. METHODS: Patients at risk of developing AKI (history of diabetes and/or anaemia; estimated glomerular filtration rate 20–60 ml/min/1.73 m 2 ; anticipated CPB time >120 min; log EuroSCORE > 5) were randomized to the RG system group ( n = 110) or managed according to current practice (control = 110). The primary end point was the development of AKI within the first 3 postoperative days as defined by the RIFLE (Risk, Injury, Failure, Loss of kidney function, End-stage renal disease) criteria. RESULTS: There were no significant differences in preoperative and intraoperative characteristics between the 2 groups. Postoperative AKI rates were significantly lower in the RG system group compared to the control group [10% (11/110) vs 20.9% (23/110); P = 0.025]. This effect persisted even after controlling for a number of potential confounders (odds ratio 2.82, 95% confidence interval 1.20–6.60; P = 0.017) when assessed by binary logistic regression analysis. The mean volumes of urine produced during surgery and within the first 24 h postoperatively were significantly higher in the RG system group ( P < 0.001). There were no significant differences in the incidence of blood transfusions, atrial fibrillation and infections and in the median duration of intensive care unit stays between the groups. The number needed to treat with the RG system to prevent AKI was 9 patients (95% confidence interval 6.0–19.2). CONCLUSIONS: In patients at risk for AKI who had cardiac surgery with CPB, the RS RG system significantly reduced the incidence of AKI and can be used safely and reproducibly. Larger studies are required to confirm cost benefits. Clinical trial registration number: NCT02974946